2015
DOI: 10.1503/jpn.140246
|View full text |Cite
|
Sign up to set email alerts
|

Baseline brain perfusion and brain structure in patients with major depression: a multimodal magnetic resonance imaging study

Abstract: IntroductionIn the past 2 decades, functional and structural neuroimaging techniques have been developing rapidly, yielding a large body of research addressing neural correlates of major depressive disorder (MDD). Neuroimaging has substantially shaped our understanding of depressive etiopathology, indicating its potential to become an objective tool of diagnostic, therapeutic and prognostic value.1 In MDD, first neuroimaging studies examined cerebral metabolism by means of positron emission tomography (PET). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 84 publications
4
40
1
Order By: Relevance
“…However, in the present study, cerebral blood hyper-perfusion tended to be located in the right brain hemisphere, which is inconsistent with certain previous studies (7,25). Our current findings and the findings of previous studies indicate a sophisticated phenomenon; however, this is not surprising, as the results of the different studies may have been influenced by various confounding factors, such as differences in clinical characteristics of the participants, effects of antidepressants on the participants, and the technical characteristics of image acquisition and analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the present study, cerebral blood hyper-perfusion tended to be located in the right brain hemisphere, which is inconsistent with certain previous studies (7,25). Our current findings and the findings of previous studies indicate a sophisticated phenomenon; however, this is not surprising, as the results of the different studies may have been influenced by various confounding factors, such as differences in clinical characteristics of the participants, effects of antidepressants on the participants, and the technical characteristics of image acquisition and analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings of GM and δrCBV are not symmetric. This is similar to the lateralized effects in brain structural changes (24) and those in cerebral blood volume changes (22) related to breeding of depressive-like behavior.…”
Section: Biological Implicationssupporting
confidence: 72%
“…in limbic and prefrontal cortex structures. Another study showed changes of cerebral blood flow and brain volume co‐occurring in patients with major depressive disorder . Short‐term effects of rCBV alterations are caused by swelling of capillaries, whereas long‐term effects occur due to changes in the capillary bed, like angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In major depression disorder (MDD), Vasic N. et al(88) suggest that while changes of cerebral blood flow (brain perfusion) and GM volume co-occur in MDD patients, they appear to reflect distinct levels of neuropathology. Dutt A et al(89) reported P300 latency, a measure of the speed of neural transmission, appeared to relate to the size of left hippocampus in schizophrenia, but not in psychotic bipolar disorder.…”
Section: Review Of Fusion Studies Focused On Psychopathologymentioning
confidence: 99%